Nanostructured Antimicrobials in Food Packaging—Recent Advances - Azeredo, Henriette M. C.; Otoni, Caio G.; Corrêa, Daniel S.; Assis, Odílio B. G.; de Moura, Márcia R. [UNESP]; Mattoso, Luiz Henrique C. (Wiley, 2019)
Active food packaging systems promote better food quality and/or stability, such as by releasing antimicrobial agents into food. Advantages of adding antimicrobials to the packaging material instead of into the bulk food include controlled diffusion, reduced antimicrobial contents, and improved cost effectiveness. Nanostructured antimicrobials are especially effective due to their high specific surface area. The present review is focused on recent advances and findings on the main nanostructured antimicrobial packaging systems for food packaging purposes. Several kinds of nanostructures, including both inorganic particles and organic structures, have been proven effective antimicrobials by different mechanisms of action and with different application scopes. Moreover, there are systems containing nanocarriers to protect antimicrobials and deliver them in a controlled fashion. On the other hand, scientific data about migration of nanostructures onto food and their toxicity are still limited, requiring special attention from researchers and regulation sectors.
Keywords: metal oxides; montmorillonite; nanoencapsulation; polymers; silver nanoparticles